Literature Review: Etnomatematika Pada Motif Batik Indonesia - Jeranah, Jeranah; Ilmi, Nurul (Universitas Cokroaminoto Palopo, 2025)
Batik is a noble cultural heritage of the Indonesian nation. Ethnomathematics in batik culture has been widely explored by mathematics education researchers. The purpose of this study is to conduct a literature review on ethnomathematics in batik motifs. The research method used is SLR (Systematic Literature Review). Data collection was carried out by exploring articles related to ethnomathematics in traditional houses published in the period 2018 to 2021. The articles used in the study were 5 accredited national articles obtained from Google Scholar using the Publish or Peris application. Based on the results of the literature review study, it was concluded that the results of ethnomathematics studies on batik motifs that have been carried out by Indonesian researchers can be used as realistic mathematics learning materials that effectively improve students' mathematics abilities in learning.